Recommendations on biomarker bioanalytical method validation by GCC. (October 2012) - Hougton, Richard; Gouty, Dominique; Allinson, John; Green, Rachel; Losauro, Mike; Lowes, Steve; LeLacheur, Richard; Garofolo, Fabio; Couerbe, Philippe; Bronner, Stéphane; Struwe, Petra; Schiebl, Christine; et al.
The 5th GCC in Barcelona (Spain) and 6th GCC in San Antonio (TX, USA) events provided a unique opportunity for CRO leaders to openly share opinions and perspectives, and to agree upon recommendations on biomarker bioanalytical method validation.